FORECASTING PENJUALAN OBAT PADA APOTEK DENGAN METODE EXPONENTIAL SMOOTHING MENGGUNAKAN RSTUDIO (Studi Kasus Apotek Naldifa Babelan) - Bintang Pramudya; Ruiz Anggie; Paduloh (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
Medicines are important products in maintaining human health. The need for medicines will continue to increase along with population growth and lifestyle changes. Therefore, pharmacies need to forecast drug sales to ensure adequate drug availability and avoid excess or shortage of stock. This research aims to apply the Exponential Smoothing method in predicting drug sales in pharmacies using RStudio drug sales software which uses historical data on drug sales during a certain period. The results of this research indicate that the Triple Exponential Smoothing method is the best method to use because it has results with an SSE value of 3,508.75, when compared with the Single Exponential Smoothing and Double Exponential Smoothing methods with a value of 10,306.39